Highly Functionalized Pyrrolylpyridines from 2-(Acylethynyl)-pyrroles - Tomilin, Denis N.; Sobenina, Lyubov N.; Ushakov, Igor A.; Trofimov, Boris A. (Synthesis, 2020)
A novel family of pharmaceutically prospective, densely functionalized (aryl-, hetaryl-, acyl-, and vinyl-substituted) pyrrolylpyridines has been assembled in up to 95% yields via the amination (NH4Cl/K2CO3/DMSO system, 90 °C, 16 h) of 2-(acylethynyl)pyrroles, followed by cyclization (MeOH, reflux, 6 h, up to 90% yield) of the formed intermediate 1-(pyrrol-2-yl)-1-aminoenones with acetylenic ketones (Bohlmann–Rahtz reaction). The intermediate pyrrolyl aminodienones, prospective building blocks for organic synthesis, can be separately synthesized (DMSO, 90 °C, 6 h) in 70–86% yields. A novel facet of this chemistry is stereoselective synthesis of C-vinylated pyridines, (E)-3-[5-acyl-2-aryl-6-(pyrrol-2-yl)pyridin-3-yl]-1-arylprop-2-en-1-ones, by involving the second molecule of acylacetylene into the reaction.
Keywords: 2-(acylethynyl)pyrroles; 1-(pyrrol-2-yl)-1-aminoenones; acetylenic ketones; aminodienones; intramolecular cyclization; pyrrolylpyridines